The emission cost of international sourcing: using structural decomposition analysis to calculate the contribution of international sourcing to CO2-emission growth. Issue 2 (2nd April 2016) - Hoekstra, Rutger; Michel, Bernhard; Suh, Sangwon
ABSTRACT: The effect of changes in trade patterns, particularly increasing international sourcing, on global CO2 -emissions growth has yet to be clearly understood. In this paper, we estimate the emission cost of sourcing (ECS), which originates from replacing domestic products by imports from countries with more CO2 -intensive technologies. Using a structural decomposition analysis, we find that changes in sourcing patterns between 1995 and 2007 contribute (1) to reducing territorial emissions in high-wage countries (70% of their territorial emissions growth) and (2) to increasing territorial emissions in low-wage countries (30% of their territorial emissions increase). The net global effect, the ECS, amounts to 18% of total global CO2 -emissions growth. Our results call the climate change policies based on territorial principles into question given that they disregard that differences in emission intensities between countries contribute to raising global emissions. In contrast, policies fostering the transfer of cleaner technologies to low-wage countries decrease the ECS.